(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
This article talks about the economic foundations of the Kashkadarya region, the role of agriculture, cotton growing, cattle breeding and industry in the oasis and the republic. The results of reforms carried out in subsequent years in all areas were also analyzed.